Blending Lines in TEFL: Attaining Literacy Thru Scientific Approach - rohib adrianto sangia (Jurnal CULTURE (Culture, Language, and Literature Review), 2016)
This writing is trying to elaborate Government’s policy in teaching English of primary and secondary school in Indonesia. The literacy has been developed not only read and write but also furthermore use the knowledge in order to help student role in society. It is revealing some theories and techniques that are supporting the literacy approach until in the classroom. It is suggested to the teacher to enrich not only their capacity in the professional competencies but also developing their pedagogy capacity in order to implementing national curriculum 2013 that is projected to change the language teaching paradigm from literacy approach which gives the students opportunity to use the information from what they read and write to scientific approach that gives students chance to develop their intelligence to higher order thinking in learning language and expected in using it in proper way as life skills equipment in facing the rapid changes of global society system in the near future. In brief, it can be determined that scientific approach is in the language learning process environment; meanwhile literacy approach is concerned to the language learning results framework. It is expected that teachers can understand and act in the classroom as the literate teacher.  Keywords: Literacy skills, scientific approach, TEFL curriculum.